Thermal Performance of Lightweight Steel Framed Facade Walls Using Thermal Break Strips and ETICS: A Parametric Study - Santos, Paulo (2023)
The thermal performance of lightweight steel framed (LSF) facade walls depends on many factors, such as the steel studs, the batt insulation, the external thermal insulation composite systems (ETICS), and the sheathing layers. Moreover, the high thermal conductivity of steel could negatively affect their thermal performance due to the consequent thermal bridge effect. Furthermore, in LSF walls, the batt insulation is usually bridged by the steel studs. Thus, some analytical calculation procedures defined in standards (e.g., ISO 6946) are not valid, further complicating their thermal performance quantification. In this research, a parametric study to evaluate the thermal performance of facade LSF walls is presented. Seven relevant parameters are assessed, most of them related to the use of thermal break strips (TBS) and ETICS. The 2D numerical models used to predict the conductive R-values were experimentally validated, and their precision was successfully verified. As earlier found in a previous research work for partition LSF walls, it is also more effective for facades to increase the TBS thickness rather than their width, with the R-value increments being slightly smaller for facade LSF walls. These features were more pronounced for double TBS and for the smaller stud spacing (400 mm). The major thermal performance improvements were found when increasing the ETICS insulation thickness and decreasing their thermal conductivity.